Beirut Rapid Damage and Needs Assessment - World Bank Group (World Bank, Washington, DC, 2020)
On August 4, 2020, a massive explosion rocked the Port of Beirut (PoB), destroying much ofthe port and severely damaging dense residential and commercial areas within five kilometersof the site of the explosion. The disaster left more than 200 people dead, thousands injured, andmany homeless. Shocking pictures and videos from the Lebanese capital were shared widely acrossthe planet, showing a city in ruins and the suffering of those affected. Beyond the human tragedy, the economic impact of the explosion is notable at the national level despite the geographic concentration of the destruction. This reflects: (i) the demographic clustering of the Lebanese population in Beirut and its suburbs; (ii) the prominence of economic activity in the affected areas, especially in regard to commerce, real estate and tourism; and (iii) the fact that the PoB is the main point of entry/exit for the small open economy, channeling 68 percent (2011-2018 average) of the country’s total external trade. Even prior to the explosion, Lebanon was already reeling from multiple crises since 2011. These included: (i) spillovers from the conflict in Syria, which led Lebanon to host the largest refugee per capita population in the world; (ii) a financial and economic crisis that has induced systemic macrofinancial failures, including, impairment of the banking sector and risk of deposits; an exchange rate collapse; a default on sovereign debt; triple digit inflation rates; and a severe economic contraction; and (iii) impacts from the COVID-19 pandemic; Lebanon, not unlike other countries, responded with lockdowns that further exacerbated economic and financial stresses. The above add to long-term structural vulnerabilities that include low-grade infrastructure—a dysfunctional electricity sector, water supply shortages, inadequate solid waste and wastewater management—public financial mismanagement, large macroeconomic imbalances, and deteriorating social indicators. These vulnerabilities are taking place against the backdrop of high levels of corruption, political turmoil, and weak governance. Internationally, Lebanon was sub-optimally integrated into the global economy and global value chains, and the sizeable and persistent migration of highly educated human resources to foreign labor markets (brain drain) further contributed to poor productivity. As a result, the economy has struggled to reduce poverty and to generate inclusive growth, with job creation remaining weak and poorly distributed even during periods of high GDP growth. The long-run employment-growth elasticity is estimated to be 0.2,2 much lower than an estimated MENA average of 0.5.3 Meanwhile, the generated employment has been concentrated in low productivity activities as those involving higher productivity have not grown proportionally. Since foreign labor dominated low skilled (less productive) activities, high GDP growth rates have not translated into significant job creation for the Lebanese.